2008
DOI: 10.1177/0011000008319985
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Burnout and Career Choice Satisfaction in Counseling Psychology Graduate Students

Abstract: Counseling psychology doctoral students ( N = 284) from 53 training programs throughout the United States anonymously completed online measures of burnout, career choice satisfaction, global stress, role conflict, social support (from family/friends, advisors, other students) and psychological sense of community (SOC) in the doctoral program. Two hierarchical multiple regressions were performed to test hypotheses that social support would buffer the effects of stress on burnout and career choice satisfaction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 71 publications
6
44
1
2
Order By: Relevance
“…Preliminary evidence found high burnout was associated with coping by excessively dwelling on one's emotions (emotion‐focused) or avoiding one's emotions (avoidant‐coping) (Ackerley et al., ; Cushway & Tyler, ; Huebner, ; Wilkerson, & Bellini, ), potentially due to reduced opportunities for interpersonal connection and social support (Huebner, ). There were mixed findings on the role of social support, but the majority of studies identified that social support alongside personal therapy, was correlated with high burnout among psychotherapists (Darongkamas et al., ; Kahill, ; Ross et al., ; Stevanovic, & Rupert, ), although it is probable that they were accessing personal therapy as a consequence of (rather than predictor of) burnout (Darongkamas et al., ; Di Benedetto & Swadling, ; Kovach Clark, Murdock, & Koetting, ). A study by Rzeszutek and Schier () posited that perceptions of social support were stronger predictors of burnout than actual social support itself, whereby social support may only be protective if the psychotherapist feels supported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preliminary evidence found high burnout was associated with coping by excessively dwelling on one's emotions (emotion‐focused) or avoiding one's emotions (avoidant‐coping) (Ackerley et al., ; Cushway & Tyler, ; Huebner, ; Wilkerson, & Bellini, ), potentially due to reduced opportunities for interpersonal connection and social support (Huebner, ). There were mixed findings on the role of social support, but the majority of studies identified that social support alongside personal therapy, was correlated with high burnout among psychotherapists (Darongkamas et al., ; Kahill, ; Ross et al., ; Stevanovic, & Rupert, ), although it is probable that they were accessing personal therapy as a consequence of (rather than predictor of) burnout (Darongkamas et al., ; Di Benedetto & Swadling, ; Kovach Clark, Murdock, & Koetting, ). A study by Rzeszutek and Schier () posited that perceptions of social support were stronger predictors of burnout than actual social support itself, whereby social support may only be protective if the psychotherapist feels supported.…”
Section: Discussionmentioning
confidence: 99%
“…Personality factors associated with stress and burnout included neuroticism (Hellman et al, 1987b;Lent & Schwartz, 2012;Mills, & Huebner, 1998) rigid thinking style (Emery, Wade, & MacLean, 2009); excessive conscientiousness, overinvolvement in client problems (Ackerley et al, 1988;Rupert & Kent, 2007;Rupert & Morgan, 2005;Rzeszutek & Schier, 2014;Steel, Macdonald, Schroder, & Mellor-Clark, 2015); perfectionism and a tendency to strive to meet high self-expectations, (Cushway, 1992;D'Souza, Egan, & Rees, 2011;Emery et al, 2009;Kovach Clark, Murdock, and Koetting, 2009;Papadomarkaki, & Lewis, 2008). However, low trait agreeableness, "disagreeable" traits (e.g., egocentrism, less compassion, competitiveness), low extraversion (Huebner, & Mills, 1994;Lent & Schwartz, 2012;Mills, & Huebner, 1998) and high introverted traits (e.g., shyness), were also associated with higher job stress due to less interpersonal connection with clients, limited avenues of collaboration with colleagues, and fewer opportunities for social support (Beaumont et al, 2016;Finlay-Jones, Rees, & Kane, 2015;Huberty, & Huebner, 1988).…”
Section: Personality and Personal Beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…These supportive relationships are helpful for graduate students to cope with stress (Clark, Murdock, & Koetting, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This scholarship, while important to inform policy within the profession, has left largely unaddressed the personal effect on internship applicants. Although graduate training is known to be stressful (Clark, Murdock, & Koetting, 2008;Dearing, Maddux, & Tangney, 2005), a recent report suggests that the experience of going unmatched is particularly difficult (Hogan et al, 2014). In that study, applicants' subjective well-being was assessed before and after match notification.…”
Section: Doctoral Internshipsmentioning
confidence: 99%